Pengaruh Iklim Organisasi, Budaya Kerja dan Motivasi terhadap Kinerja Pegawai pada Dinas Kebudayaan dan Pariwisata Provinsi Papua Barat - Febianus Heatubun; Ketut Widiarta (Insan Cita Bongaya Research Journal, 2025)
This research aims to analyze the Influence of Organizational Climate, Work Culture, and Motivation on Employee Performance. This research approach uses a quantitative approach with primary data through the distribution of questionnaires to 35 employees of the Office of Culture and Tourism of West Papua Province. To measure the direct influence of the variables of Organizational Climate, Work Culture, and Motivation on Employee Performance with the help of analysis tools using SPSS v.25. The results of the study show that the variables of Organizational Climate (t count 7.538 > 1.695 and sig value 0.000 < 0.05), Work Culture (t count 6.205 > 1.695 and sig value 0.000 < 0.05) and Motivation (t count 2.176 > 1.695 and sig value 0.040 < 0.05) have a positive and significant effect on Employee Performance. The results of the study simultaneously influenced the variables Organizational Climate, Work Culture and Motivation with F count (67.660 > 3.181) on the Performance of Employees of the Cultural Service and Tourism in West Papua Provincee